Estimating seawater intrusion impacts on coastal intakes as a result of climate change. Issue 11 (1st November 2013) - Roehl, Edwin A.; Daamen, Ruby C.; Cook, John B.
Abstract : Many coastal utilities will find it challenging to adapt to future climate conditions in which sea‐level rise and extreme weather cycles could increase the frequency and duration of seawater intrusion into estuaries. This article describes a method of assessing risk to utility water supplies and details its use in two coastal systems supplying freshwater to municipalities in Georgia and South Carolina. The method uses long‐term weather and hydrologic data to develop empirical models that represent the seawater intrusion process in the vicinity of an intake. Data available from past droughts and storms provided sufficient variability to model the range of anticipated future weather and hydrologic conditions. The model can be varied using permutations of historical conditions and climate change forecasts to estimate future impacts at the intake. The models and data are deployed in a spreadsheet program that features a graphical user interface and supporting graphics, making it readily usable by utility personnel.